The use of SMILES data to study ozone loss in the Arctic winter 2009/2010 and comparison with Odin/SMR data using assimilation techniques - Sagi, K.; Murtagh, D.; Urban, J.; Sagawa, H.; Kasai, Y. (Atmospheric Chemistry and Physics, 2014)
The Superconducting Submillimeter-Wave Limb-Emission Sounder (SMILES) on board the International Space Station observed ozone in the stratosphere with high precision from October 2009 to April 2010. Although SMILES measurements only cover latitudes from 38° S to 65° N, the combination of data assimilation methods and an isentropic advection model allows us to quantify the ozone depletion in the 2009/2010 Arctic polar winter by making use of the instability of the polar vortex in the northern hemisphere. Ozone data from both SMILES and Odin/SMR (Sub-Millimetre Radiometer) for the winter were assimilated into the Dynamical Isentropic Assimilation Model for OdiN Data (DIAMOND). DIAMOND is an off-line wind-driven transport model on isentropic surfaces. Wind data from the operational analyses of the European Centre for Medium- Range Weather Forecasts (ECMWF) were used to drive the model. In this study, particular attention is paid to the cross isentropic transport of the tracer in order to accurately assess the ozone loss. The assimilated SMILES ozone fields agree well with the limitation of noise induced variability within the SMR fields despite the limited latitude coverage of the SMILES observations. Ozone depletion has been derived by comparing the ozone field acquired by sequential assimilation with a passively transported ozone field initialized on 1 December 2009. Significant ozone loss was found in different periods and altitudes from using both SMILES and SMR data: The initial depletion occurred at the end of January below 550 K with an accumulated loss of 0.6–1.0 ppmv (approximately 20%) by 1 April. The ensuing loss started from the end of February between 575 K and 650 K. Our estimation shows that 0.8–1.3 ppmv (20–25 %) of O3 has been removed at the 600 K isentropic level by 1 April in volume mixing ratio (VMR).